Upaya Pemberdayaan Bisnis Skala Kecil Pariwisata Bali Berkelanjutan pada Era New Normal - I Gede Sutarya; I Nengah Suardhana; I Gusti Bagus Rai Utama (Indonesian Journal of Tourism and Leisure, 2023)
Bali tourism was experiencing difficult times with minus growth during the pandemic in 2020 and 2021. In 2022, Bali tourism has’nt recovered as before yet. This proves that the Bali tourism development model based on mass tourism cannot provide comfort and security for the people of Bali. Amid this crisis, it was difficult for Balinese people to return to the agricultural sector due to the decline in agricultural land. Therefore, finding a model for tourism development in Bali for the future was a serious matter. This model must also touch on the philosophy of tourism development in Bali, namely Tri Hita Karana. The results of the analysis show that this philosophy cannot work in the context of mass tourism development. This philosophy can only work in small-scale rural tourism development. Therefore, the ideal Bali tourism model was a small-scale rural tourism model. This model was also threatened by the development of mass tourism. Therefore, the government must pay more attention to the development of small-scale tourism businesses, which were stronger in times of crisis because the small-scale business model was a model of sustainable tourism development in the new normal era.